Mannose Phosphate Isomerase Isoenzymes in Plutella xylostella Support Common Genetic Bases of Resistance to Bacillus thuringiensis Toxins in Lepidopteran Species - Herrero, Salvador (American Society for Microbiology, 2001)
A strong correlation between two mannose phosphate isomerase (MPI) isoenzymes and resistance to Cry1A toxins from Bacillus thuringiensis has been found in a Plutella xylostella population. MPI linkage to Cry1A resistance had previously been reported for a Heliothis virescens population. The fact that the two populations share similar biochemical, genetic, and cross-resistance profiles of resistance suggests the occurrence of homologous resistance loci in both species.